Determination of he-buffalo leg sinkage through simulation in laboratory and field condition to assess reaction under the hooves - KUMAR, SANTOSH; SINGH, TARUNBIR P; SINGH, JAYANT (The Indian Journal of Animal Sciences, 2013)
In spite of increasing mechanization of agricultural operations, animals remain an important source of energy for crop production in India. It is easily available source of farm power, especially in hilly regions of the state of Uttarakhand, where the land is fragmented, irregular, scattered in the form of bench terraces and not suitable for mechanization. Hebuffalosare not only used for seedbed preparation but are major source for carting the cane to sugar mills in Tarai region of this state. Different types of animal develop power differently. A good amount of work has been done on various aspects of draught animal power especially on work rest cycle in linear and rotary mode of operation but very little work has been done on how they actually produce tractive force. With this aim a study was conducted in the University to determine the he-buffalo leg sinkage through simulated wooden leg and also to assess vertical reactive force under the feet of he-buffalo under laboratory and field condition. On the basis of the study it was concluded that the animal leg sinkage increased or decreased significantly with the change in soil moisture content, soil hardness (cone index value) and magnitude of load applied. It was also observed that sinkage of the front legs of he-buffalo was more than the rear legs. Similarly the reactive force was found greater on the front legs than rear legs up to a load equivalent to 26.8% of body weight. Exceeding this load the reactive force was observed more on rear legs compared to front legs probably due to weight transfer phenomenon.